Exploring the factors driving automotive exports in OECD countries - Patrick Jochem; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
Based on data for eight OECD countries this paper empirically explores the factors driving exports in the automotive sector between 1991 and 2008. The factors considered explicitly account for possible lead market effects which have recently been identified in the literature as relevant factors in studying the export potentials of certain technologies. Econometric results suggest that exports in the automotive sector are positively related to the general strength of a country in terms of exports, to higher GDP per capita and to a lower labour cost share in the automotive sector. However, domestic market size and R&D in the automotive sector appear to have no effect on exports. Hence, the results provide only limited rationale for policy intervention.
urn:nbn:de:0011-n-1679658
Keywords: 330; Lead markets; export potentials; automotive industry; Kraftfahrzeugindustrie; Exportindustrie; Schlüsselsektor; OECD-Staaten